Tools for Analyzing Cash Flows from Investing Activities in Ukraine - Anatolii DANYLENKO; Tetyana ARBUZOVA; Larisa SATYR; Victoria NOVIKOVA; Viktoriia ZUBCHENKO; Olena VASYLENKO; Oksana BANAR (Communications of International Proceedings, 2020)
The article deals with the improvement of tools for analyzing cash flows from investments made by a company, which is topical due to the required productivity and competitiveness of business. The research puts general description and provides improved steps for analyzing cash flows generated through investing activities. By analyzing cash flows from investing activities of a company, one should take into account the full set of indicators of variable industries highly impacting the company and its life cycle. The conducted research systemized tools for analyzing cash flows from investing activities, investigates them and developed improved stages included in the analysis procedure. It can be employed for assessing the efficiency of managing the cash flows from investing activities.
Keywords: Net cash flow; cash flow from investing activities of the enterprise; the efficiency of cash flow management; analysis; cash flow optimization; synchronization cash flow sensitivity of investment of the enterprise.